Photodynamic therapy for the precise treatment of localized prostate cancer - Xu, Youcheng; Tan, Qinyuan; Sun, Chong; Jia, Yuefeng; Li, Shengxian; Yang, Xuecheng (Frontiers in Oncology, 2025)
Over the past 20 years, early diagnosis of prostate cancer has become increasingly prevalent due to the promotion of prostate-specific antigens, and its treatment has become a focal point. However, there are some drawbacks associated with therapies for early prostate cancer, such as active surveillance and radical prostatectomy, which may include urinary incontinence, erectile dysfunction, and urinary tract infection. In contrast, photodynamic therapy (PDT) is introduced into the treatment of prostate cancer because of its advantages, such as high precision to tumor cells, low toxicity, and no radiation. Compared to radical prostatectomy, the PDT has low risk and minimal trauma. Although PDT is in the early stages of clinical development, it holds promise for the effective treatment of localized prostate cancer. Herein, we reviewed studies on the mechanisms of PDT and photosensitizers for prostate cancer. Given the rapid development of nanotechnology, photosensitizers wrapped by nanomaterials have emerged as new option with significant advantages, particularly of in achieving high tumor selectivity using functional nanomaterials. Numerous PDT clinical trials on prostate cancer have been conducted worldwide. We also reviewed the results of a few photosensitizers in these clinical trials. However, a few limitations and challenges regarding PDT for prostate cancer still exist. In addition, future development and potential clinical application strategies of future PDT are predicted.